Knowledge, Attitude, and Medicine Taking Behavior of Lymphatic Filariasis Patients in Two Villages in West Kotawaringin Regency - Yuniarti Suryatinah; Nita Rahayu (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Kotawaringin Barat Regency carried out the lymphatic filariasis mass drug administration (LF MDA) and in 2016 it was declared to have passed the 3rd transmission assessment survey (TAS). One success factor of 3rd TAS is behavior of adherence to taking preventive drugs from community participated. The purpose of this article is to analyze the relationship between knowledge and attitude of adherence to taking filariasis prevention drugs in two villages in West Kotawaringin Regency. The study was conducted in 2017 using an observational design with a cross-sectional approach. The samples used were 273 people ≥ 15 years. The instrument is a questionnaire of knowledge, attitudes and behavior related to LF MDA. Respondent characteristics and knowledge description were analyzed descriptively. Then chi square test was carried out to determine the relationship between gender, age, education, knowledge and attitudes towards drug-taking behavior. The results of the study found that the percentage of respondents in West Kotawaringin Regency who had good knowledge is 58.2%, the number of respondents with good attitudes is 66.7% and 89.4% of them behaved obediently in taking preventive drugs filariasis. Gender (p = 0.794), age (p = 0.372), education (p = 0.263), knowledge (p = 0.536) and attitude (p = 0.765) were not significantly related adherence behavior to taking filariasis prevention drugs. The conclusion of the study is that there are other factors other than gender, age, education, knowledge and attitude that can affect the behavior of adherence to taking filariasis prevention drugs in two villages in West Kotawaringin Regency.